Step-cut, biplanar, elongation and angulation ulnar osteotomy with annular ligament reconstruction in neglected Monteggia fracture dislocation in children: a retrospective study - Garg, Rohit Nirbhay; Gupta, Dinesh; Kundu, Soutrik; Vaje, Shweta Sonu (International Journal of Research in Orthopaedics, 2023)
Monteggia fracture dislocation is an infrequent injury in children, with around 20-50% cases being missed on initial consultation; leading to their chronic and neglected forms leading to number of complications; thus justifying their operative management. Various treatment modalities have been suggested in the literature for these neglected injuries. A retrospective study of 7 patients (5 males and 2 females), with mean age of 9.58 years (7-14 years); with neglected Monteggia fracture dislocation undergoing corrective reconstructive surgery in the form of elongation and angulation proximal ulnar osteotomy with radial head reduction combined with annular ligament reconstruction was conducted and was then evaluated clinically and functionally using Mayo Elbow Performance Index (MEPI) score; and radiographicaly were graded as good, moderate or poor. The mean interval from time of injury to the time to corrective surgery was 10.58 weeks (range 6-16 weeks). The mean improvement in the post operative MEPI score was 23.57. The mean improvement in the post operative flexion-extension arc was 28.57˚, while that in the supination-pronation arc was 20.72˚. We concluded that Step-cut, biplanar, elongation and angulation proximal ulnar osteotomy with additional reinforcement in the form of annular ligament reconstruction is an effective technique to treat neglected Monteggia fracture dislocations in children; having excellent clinical, functional and radiological outcomes.